Biodiesel production using fatty acids from food industry waste using corona discharge plasma technology. (January 2016) - Cubas, A.L.V.; Machado, M.M.; Pinto, C.R.S.C.; Moecke, E.H.S.; Dutra, A.R.A.
Highlights: The reactions were carried out in catalysts absence and the alcohol was methanol. The Rf value of 0.8 verified the formation of methyl esters. The methyl ester can be obtained in chemical catalysts absence and no co-products. Abstract: This article aims to describe an alternative and innovative methodology to transform waste, frying oil in a potential energy source, the biodiesel. The biodiesel was produced from fatty acids, using a waste product of the food industry as the raw material. The methodology to be described is the corona discharge plasma technology, which offers advantages such as acceleration of the esterification reaction, easy separation of the biodiesel and the elimination of waste generation. The best conditions were found to be an oil/methanol molar ratio of 6:1, ambient temperature (25 °C) and reaction time of 110 min and 30 mL of sample. The acid value indicates the content of free fatty acids in the biodiesel and the value obtained in this study was 0.43 mg KOH/g. Peaks corresponding to octadecadienoic acid methyl ester, octadecanoic acid methyl ester and octadecenoic acid methyl ester, from the biodiesel composition, were identified using GC–MS. A major advantage of this process is that the methyl ester can be obtained in the absence of chemical catalysts and without the formation of the co-product (glycerin).